Description and management of Aspergillus section Nigri causing post-harvest bulbs rot of onion - Eman G. A. M. El-Dawy; Mohamed A. Hussein; Safaa El‑Nahas (Scientific Reports, 2024)
Abstract When onions are improperly stored, a post-harvest disease known as black mold of onion bulbs can result in considerable economic losses. Aspergillus section Nigri, one of many species, has been implicated in the development of black mold. In the present study, rot onion bulbs were collected from markets in Qena, Egypt. Thirteen Aspergillus section Nigri isolates were obtained and identified by morphological and molecular characterization. The ochratoxins potential of isolated A. section Nigri was tested, and three isolates were producers at the range of 1.5–15 ppm. For the presence of pks gene, no amplification product was detected. Using the fungal growth inhibition test, the isolates of A. niger were inhibited by eco-friendly materials Cement and Zeolite. Cement exhibited maximum percentage growth inhibition against the tested isolates at 74.7–86.7%. The pathogenicity activity of the A. niger isolates was tested by inoculation of healthy onion bulbs, other onion bulbs covered with Cement and Zeolite before inoculation by A. niger was used. The two treatments significantly reduced bulbs rot disease of onion than untreated bulbs. Seven and nine isolates showed 0% rot on covered bulbs by Cement and Zeolite, respectively as compared with inoculated onions, which exhibited rot ranging from 55 to 80%. Using eco-friendly materials with efficiency against post-harvest bulbs rot of onion was evaluated in this study.